Answer:
Explanations:
To get the equation of the oblique asymptote of a function, we will first have to get the quotient of the given function. Given the function:
![h(x)=(x^2-x-2)/(x+1)](https://img.qammunity.org/2023/formulas/mathematics/college/8k3qhkneppo1j1s3z2sywd9w8a7q0fc99b.png)
Factoring the numerator and simplifying will give;
![\begin{gathered} h(x)=(x^2-2x+x-2)/(x+1) \\ h(x)=((x^2-2x)+(x-2))/(x+1) \\ h(x)=(x(x-2)+1(x-2))/(x+1) \\ h(x)=\frac{\cancel{(x+1)}(x-2)}{\cancel{x+1}} \\ h(x)=x-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/e6wblgbdj0ka0neugc7prpv4jwsian7w1i.png)
The equation of the oblique asymptote is the first two terms of the quotient that is x - 2